2016
DOI: 10.1177/1357633x15610721
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone hearing screening in mHealth assisted community-based primary care

Abstract: Introduction: Access to ear and hearing health is a challenge in developing countries, where the burden of disabling hearing loss is greatest. This study investigated community-based identification of hearing loss using smartphone hearing screening (hearScreen TM) operated by community health workers (CHWs) in terms of clinical efficacy and the reported experiences of CHWs. Method: The study comprised two phases. During phase one, 24 CHWs performed community-based hearing screening as part of their regular hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 40 publications
(118 reference statements)
3
96
0
Order By: Relevance
“…Results and corresponding noise levels analyzed on the centralized cloud-based server indicated that only noise levels at 1 kHz had a significant effect on referral rates obtained in comparison to 2 and 4 kHz test frequencies. Previous studies using the hearScreen TM application also reported similar effects when testing at the lower frequency of 1 kHz [2123]. …”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Results and corresponding noise levels analyzed on the centralized cloud-based server indicated that only noise levels at 1 kHz had a significant effect on referral rates obtained in comparison to 2 and 4 kHz test frequencies. Previous studies using the hearScreen TM application also reported similar effects when testing at the lower frequency of 1 kHz [2123]. …”
Section: Discussionsupporting
confidence: 53%
“…Increasing screening intensities to 30 dB HL at 1 kHz to compensate for high noise levels in future community-based studies could reduce the incidence of exceeded MPANLs and false-positive results, but may decrease the validity of the screening process as mild losses may be missed [23,29]. The European Consensus Statement on Hearing, Vision, and Speech Screening in Pre-School and School-age Children indicated that although hearing screenings will produce over-referrals, false positives are preferred over false negatives [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of the study indicated that, of the 5 children who failed the screening due to noise, 3 of these children did in fact have a hearing loss (Mahomed-Asmail et al, 2016b). Furthermore, a study conducted by Yousuf Hussein, Swanepoel, Biagio de Jager, Myburgh, Eikelboom & Hugo (2015) found that, in children, exceeded MPANLs had a significant impact on passing or failing the hearing screening. However, in adults, exceeded MPANLs did not impact the outcome of the hearing screening (Yousuf Hussein et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…He proposed and validated the ability of using the tablet for hearing assessment. Shouneez, et al [21] investigated the community-based identification of hearing loss using smartphone. He found that smartphone-based hearing screening allowed community health workers to bring hearing health care to undeserved communities at the primary care level.…”
Section: Introductionmentioning
confidence: 99%